Integrating Design Thinking into Science Education: A Systematic Literature Review - Risya Pramana Situmorang; Miranita Khusniati; Panggih Priyambodo; Winarto Winarto; Sefni Oemolos (Jurnal Pemberdayaan Masyarakat, 2026)
The accelerating trend of applying Design Thinking (DT) in modern science education has not been accompanied by enough investigation into its effectiveness among different types of learning environments. Using the PRISMA approach, an SLR of SCOPUS-indexed papers from 2015 to 2025 is conducted to investigate global trends, methodological perspectives, and challenges in DT integration. Thirty-two eligible articles were identified and analyzed bibliometrically using VOSviewer Explorative research. Findings – An obvious surge in publications involving DT has been observed since 2019, with qualitative methods most widely used in recent years, especially case studies and design-based research. Case-based or collaborative learning, supported by digital tools such as prototyping platforms and simulations, is also a suitable means for integrating DT. Some of the issues revolve around constraints on interdisciplinary research and the application of DT within content-driven curricula. The study proposal shows a need for integrated tools and hybrid pedagogical scenarios to facilitate the implementation and assessment of DT. Implications for science education include presenting an evidence-based model for embedding DT across diverse inquiry contexts to support students in developing creative capabilities, problem-solving skills, and readiness to tackle complex scientific challenges.